Manufacturing and characterization of hybrid composites for space applications - Kam, Kenneth Keen Chong (2016)
This final year project aims at investigating the mechanical properties of electrically non-conductive hybrid composites (thin NCF carbon C-Ply™, woven Kevlar, and woven E-glass fabrics in combination with thermosetting epoxy resin- Epolam 5015) for space applications.